The effects of perceived and received support on objective performance outcome - Freeman, P.; Rees, T. (European Journal of Sport Science, 2008)
In this study, we examined the main and stress-buffering effects of perceived and received support on objective performance outcome. The sample consisted of 123 British male high-performance golfers with a mean age of 25.3 years (s=5.4). Participants completed measures of perceived support, stressors, stress, and received support before competitions. After the competitions, performance outcome (number of shots) was recorded. When the two types of support were considered separately, there were significant main effects for perceived (DeltaR2=0.08, b=-0.81, P<0.01) and received support (DeltaR2=0.05, b=-0.68, P<0.01) on performance. There were also significant stress-buffering effects for perceived (DeltaR2=0.03, b=-0.48, P=0.02) and received support (DeltaR2=0.06, b=-0.61, P<0.01). When both types of support were considered together, the significant main effect (DeltaR2=0.09, P<0.01) was primarily attributable to perceived support (b=-0.63, P=0.02). The significant stress-buffering effect (DeltaR2=0.06, P=0.01) was primarily attributable to received support (b=-0.56, P=0.04). These results demonstrate the beneficial influence of social support on performance. The findings highlight the need to recognize the distinction between perceived and received support, both in terms of theory and the design of social support interventions with athletes.